Biohydrogen production from palm oil mill effluent (POME) using immobilized mixed culture (SLUDGE) - Nur Fahriza , Mohd Ali (2013)
The cell immobilization techniques by using immobilized anaerobic sludge as the seed culture were used to generate hydrogen. The substrate carbon source was taken from Palm Oil Mill Effluent (POME). It was revealed that by using the same concentration of POME, the suspended cell reactor was able to produce hydrogen at an optimal rate of 0.349111-12/1 POME at HRT 6 h. However, the immobilized cell reactor was able to exhibit better hydrogen production rate at 0.587 1 I H2/I P0MB h at HRT 2 h. The present of beads enhanced the production of hydrogen during lower HRT without encountering wash out of cell. This could be shown by higher production of hydrogen at HRT 1 h with 0.53 5 I H2/I POME by using immobilized cell reactor. Compared to suspended cell reactor, the production of hydrogen at HRT 1 h was very low with 0.092 1112/1 POME due to wash out of cell during this time. The side products during hydrogen production were soluble metabolites including butyric acid and acetic acid, followed by propionic acid and ethanol.